Psychological impact and the effort of da'i handling victims of sexual violence in adolescents - Ali Murtadho; Muhammad Taufik Hilmawan (Jurnal Ilmu Dakwah, 2022)
Purpose - The purpose of this study is to determine the psychological impact of victims of sexual violence and the da'i efforts carried out by the preacher, in this case, the counselor with an individual approach to dealing with victims of sexual violence.Method - This research uses qualitative research using a case study approach. The research subjects were 2 supervisors who handled 14 victims within 3 months. In addition, observations of the subject, and interviews with counselors and psychologists outside the LRC-KJHAM (Legal Resource Center- Keadilan Jender Hak Asasi Manusia) legal aid division were also carried out, while documentation was taken from the client record or counseling status of the research subject.Result - The results of this study indicate the psychological impact that appears on victims of sexual violence: experiencing emotional disturbances, behavioral disorders, and cognitive disorders. Counselors' efforts in dealing with victims are in the form of individual counseling and group counseling in the form of support groups, and if necessary, there are interventions carried out by counselors and psychologists in handling follow-up related to handling victims.Implication – This research suggests the importance of improving the performance of da'í in this case counselors which is a da'wah effort carried out to overcome the problem of victims of sexual violence.Originality – This research is a study of how preachers try to provide awareness and motivation so that victims of violence can accept this situation as fate and find the best solution to live their daily lives.***Tujuan – Tujuan dari penelitian ini adalah untuk mengetahui dampak psikologis korban kekerasan seksual dan upaya da'i yang dilakukan oleh da'i dalam hal ini konselor dengan pendekatan individual dalam menangani korban kekerasan seksual.Metode – Penelitian ini menggunakan penelitian kualitatif dengan pendekatan studi kasus. Subjek penelitian adalah 2 orang supervisor yang menangani 14 korban dalam kurun waktu 3 bulan. Selain itu juga dilakukan observasi terhadap subjek, wawancara dengan konselor dan psikolog di luar divisi bantuan hukum LRC-KJHAM, sedangkan dokumentasi diambil dari catatan klien atau status konseling subjek penelitian.Hasil - Hasil penelitian ini menunjukkan bahwa dampak psikologis yang muncul pada korban kekerasan seksual: mengalami gangguan emosional, gangguan perilaku, dan gangguan kognitif. Upaya konselor dalam menangani korban berupa konseling individu dan konseling kelompok berupa support group, dan bila perlu ada intervensi yang dilakukan konselor dan psikolog dalam penanganan tindak lanjut terkait penanganan korban.Implikasi - Penelitian ini menyarankan pentingnya peningkatan kinerja da'i dalam hal ini konselor yang merupakan upaya dakwah yang dilakukan untuk mengatasi masalah korban kekerasan seksual.Orisinalitas – Penelitian ini merupakan kajian tentang bagaimana para da’i berusaha memberikan kesadaran dan motivasi agar korban kekerasan dapat menerima keadaan ini sebagai takdir dan mencari solusi terbaik untuk menjalani kehidupan sehari-hari.